Ethno-Religious Nationalism and the Restructuring of Citizenship in India: A Constitutional and Diplomatic Analysis - Nabila Hasna Adawiyah; Surwandono Surwandono (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
India’s 2019 Citizenship Amendment Act (CAA) and the revocation of Article 370 mark a significant shift from secular democratic principles toward ethno-religious nationalism. The CAA introduces religious criteria for citizenship by offering expedited naturalization to non-Muslim minorities from Pakistan, Afghanistan, and Bangladesh, while deliberately excluding Muslims. Simultaneously, Article 370’s revocation dismantled the constitutional autonomy of Jammu and Kashmir, India’s only Muslim-majority region. This qualitative empirical study employs document analysis, comparative legal analysis, and critical discourse analysis to examine legislative texts, constitutional amendments, and academic literature. Primary data sources include constitutional document, and citizenship laws. Secondary data is drawn from indexed scholarly articles, books, and reputable media. The article uses Religious Nationalism Theory and Neoclassical Realism as its theoretical framework to analyze the domestic ideological dynamics underpinning Hindutva and the filtering mechanisms in India’s foreign policy. The study finds that the legal architecture of the CAA-NRC fosters systemic discrimination and the risk of statelessness, particularly targeting Muslims, while the removal of Article 370 undermines collective political autonomy through centralized control. Despite widespread criticism from the Organization of Islamic Cooperation, India maintains strategic partnerships with Gulf states, driven by pragmatic economic interests that outweigh pan-Islamic solidarity. This article contributes by integrating constitutional and diplomatic analysis within an ethno-religious framework, clarifying the interconnectedness of domestic policy and international relations. It fills a gap in the literature on the linkages between majoritarian domestic policies and global response, providing an analytical framework for policy development, human rights advocacy, and international relations research in pluralistic democracies.